Effects of grain‐size distribution and shape on sediment bed stability, near‐bed flow and bed microstructure. Issue 5 (16th January 2019) - Staudt, Franziska; Mullarney, Julia C.; Pilditch, Conrad A.; Huhn, Katrin
Abstract: Different studies investigating the stability of mixed sediment have found that the fine fraction can either stabilize or mobilize the bed. This study aims to find where the transition between these two modes occurs for sandy sediment and to identify the underlying (grain‐scale) processes. Flume experiments with bimodal sediment were used to investigate near‐bed processes of a non‐cohesive sediment bed, and in particular how the grain shape and the ratio of different grain sizes influence bed mobility. Medium sand ( D 50, c ≈ 400 μm) was mixed with 40 % fine material of different diameters ( D 50, f = 53; 111; 193 μm) and subjected to increasing flow velocities ( U = 1.3–22.2 cm s ‐1 ). The bed mobility (i.e. the change of the bed level over time), turbidity and near‐bed hydrodynamics were analysed. Selected results were compared with similar previous experiments with spherical glass beads. The findings indicate that, due to the complex grain shapes of natural sediment, a sand bed is more stable than a bed composed of glass beads. The grain‐size ratio RD = D c  /D f between the coarse and fine grain diameters controls whether the mixed bed is stabilized or mobilized by the presence of fines, with the transition between the modes occurring at RD = 4–5.5. Mixed beds with a very low RD < 2 behave like a unimodal bed. The results suggest that RD and grain shape influence bed roughness, near‐bed flow, bed microstructure and the flow into and through the upper bed layers, which subsequently governs bed mobility. The interplay between all these processes can explain the transition between the stabilizing effect (high RD, small pore space) and the mobilizing effect (low RD, large pore space) of a fine fraction in a grain‐size mixture. © 2018 John Wiley & Sons, Ltd. Abstract : Based on flume experiments with bimodal sand mixtures ( D 50 ≤ 410 μm) we show that the effect of the fine fraction in a mixture changes from mobilization to stabilization depending on the grain‐size ratio RD = D 50, coarse /D 50, fine . The comparison with similar experiments with spherical glass beads indicates that bed mobility decreases with grain angularity. The near‐bed flow velocities and inflow into the grain matrix depend on both grain shape and grain‐size ratio and can be related to events of increased bed mobility.